2016
DOI: 10.1002/ajmg.b.32508
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age and psychiatric disorders: A review

Abstract: We review the hypotheses concerning the association between the paternal age at childbearing and childhood psychiatric disorders (autism spectrum‐ and attention deficit/hyperactive disorder) and adult disorders (schizophrenia, bipolar‐, obsessive–compulsive‐, and major depressive disorder) based on epidemiological studies. Several hypotheses have been proposed to explain the paternal age effect. We discuss the four main—not mutually exclusive—hypotheses. These are the de novo mutation hypothesis, the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 99 publications
(229 reference statements)
5
56
0
3
Order By: Relevance
“…In this large population‐based cohort study, we found that parental age at the time of birth was associated with offspring risk of epilepsy, which is in line with recent findings from several other neuropsychiatric outcomes . In particular, we found that children born to mothers younger than 20 years and born to parental couples where paternal age exceeded maternal age by at least 5 years were at increased risk of developing epilepsy within the first 10 years of their life.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this large population‐based cohort study, we found that parental age at the time of birth was associated with offspring risk of epilepsy, which is in line with recent findings from several other neuropsychiatric outcomes . In particular, we found that children born to mothers younger than 20 years and born to parental couples where paternal age exceeded maternal age by at least 5 years were at increased risk of developing epilepsy within the first 10 years of their life.…”
Section: Discussionsupporting
confidence: 89%
“…Advanced maternal age, conversely, has been suggested to increase offspring disease risk due to increased rates of genomic alterations, higher cumulative levels of harmful environmental exposures, and higher risk of perinatal and obstetric complications . Finally, prominent hypotheses linking advanced paternal age to offspring disease risk include increased frequency of de novo mutations in the male germline, age‐related epigenetic alterations, and selection into late fatherhood by factors associated with disease risk in the child (eg, mental illness) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harsh parental physical discipline such as hitting has been linked to increased emotional and behavioral problems including aggression in adolescence (10)(11)(12)(13)(14). Paternal age is a risk factor for a range of disorders and subclinical phenotypes including low academic achievement (15), with the link to autism spectrum disorders and schizophrenia most robustly replicated (16)(17)(18)(19)(20)(21). Breastfeeding and higher parental socioeconomic status (education, income, occupation) are protective factors for a range of outcomes including educational achievement (7,8,22).…”
mentioning
confidence: 99%
“…A population registry-based study in the Netherlands found a significant association with increased paternal age for ASD, schizophrenia, and major depressive disorder, but not for bipolar disorder . Several hypotheses, including de novo mutations, epigenetic alterations, and selection into late fatherhood have been put forward to explain this paternal age effect [de Kluiver et al, 2017].…”
mentioning
confidence: 99%